Recent Advances on the Analysis of Polychrome Works of Art: SERS of Synthetic Colorants and Their Mixtures With Natural Dyes - Cesaratto, Anna; Leona, Marco; Pozzi, Federica (Frontiers in Chemistry, 2019)
The development and application of proper sample pretreatments is often a key step toward the successful analysis of dyes used as artists' materials by surface-enhanced Raman spectroscopy (SERS). Complexation of the organic colorants with metal ions to dye fabrics and produce lake pigments, as well as undesired interactions with other matrix components such as substrate, binding media, fillers, and extenders, are just some of the issues that typically complicate dye identification in minute samples from invaluable artworks and museum objects. These concerns may be addressed by using, prior to SERS analysis, ad-hoc sample pretreatments that, in addition to increasing the technique's sensitivity, favorably affect its selectivity toward certain molecules or molecular classes. The present work describes a newly developed sample pretreatment based on the use of nitric acid that has proven crucial for the successful detection of aniline and xanthene dyes–the first synthetic organic colorants to be used in printing and painting, among other art forms–in microscopic samples from works of art such as a 19th-century silk fabric, paper cut-outs by Henri Matisse, Vincent Van Gogh's Irises, and Japanese woodblock prints. This treatment promotes the hydrolysis of the dye-metal bond in mordant dyes or lake pigments, resulting in a more efficient adsorption of the dye molecules on the SERS-active substrate and, hence, enabling the acquisition of high-quality spectra. In the case of synthetic colorants, this method shows advantages over hydrolysis with hydrofluoric acid–a procedure previously established for the analysis of red lakes prepared from natural dyes. The nitric acid treatment presented here may be integrated into a multi-step methodology that, by exploiting differences in solubility of various dyes and lake pigments, has enabled for the first time to successfully characterize intentional mixtures of natural and synthetic colorants of the xanthene and anthraquinone molecular classes, i.e., eosin Y and carmine, in a selection of Japanese prints of the Meiji era. The present study paves the way for the systematic identification of synthetic dyes in objects of artistic and archeological interest, even when they are present in mixtures with natural organic colorants.